Effect Of Anting-Anting Leaf Extract (Acalypha Indica L.) On Lowering Blood Glucose Rats (Rattus Norvegicus) Induced By Sukrosa - solihah, Riyadatus; Umar Rahmadani, Rizal; Kristina, Metta (Kirana Publisher (KNPub), 2024)
Anting-anting leaves (Acalypha indica L.) are weeds that have various properties, one of which is as a lowering blood glucose levels. The chemical content contained in the form of flavonoids that function as inhibitors of α-glucosidase, maltase, α-amylase enzymes, tannin substances are also known to function as astrigents that can inhibit glucose intake is not excessive. The purpose of this study is to determine whether there is an effect of anting-anting leaf extract (Acalypha indica L.) on reducing blood glucose levels in rats (Rattus norvegicus) induced by sucrose. This research used 20 rats (Rattus norvegicus) as test animals which were divided into 5 groups. The group consisted of negative control group, positive control and 3 dose groups. The doses used were 500 mg/kgBB, 1000 mg/kgBB and 1200 mg/kgBB. Mice were made hyperglycemia with sucrose induction which was then given anting-anting leaf extract (Acalypha indica L.) according to lower glucose levels in mice. The results obtained were continued with the two-way ANOVA test and obtained significant results indicated by p < 0.05 (0.005) which showed there was a significant effect of anting-anting leaf extract (Acalypha indica L.) on reducing blood glucose levels in sucrose-induced rats (Rattus norvegicus). Significant results were continued with the post hoc test and obtained significant results.